Improving Inventory Management Practices for Consumable Supplies in MSME Laundry Businesses - Irma Juniarti; Asdaqul Qail Salam; Samsinar Samsinar; Chris Dayanti Br. Ginting S; Masnawaty Sangkala (PT. Global Research Collaboration, 2025)
Micro, Small, and Medium Enterprises (MSMEs) have a strategic role in the national economy, but often face challenges in managerial aspects, including managing consumables inventory. This study aims to analyze the consumables inventory control system at MSME Mapparennu Laundry and Dry Clean Makassar, identify the obstacles faced, and formulate effective improvement strategies. The study used a Participatory Action Research (PAR) approach which is collaborative and participatory, with data collection methods in the form of interviews, observations, documentation, and group discussions. The results of the study indicate that the control system implemented is still manual, not well documented, and not based on historical data, resulting in cost inefficiency, operational disruptions, and low accountability. Some of the main obstacles found include the lack of a recording system, the absence of SOPs, and low awareness and capacity of human resources. To overcome this, it is recommended to implement a simple digital recording system, prepare SOPs, data-based needs planning, periodic supervision, employee training, and optimize storage space. This strategy is expected to improve operational efficiency and the effectiveness of MSME internal control, as well as become a learning model for other similar businesses.